Rasialisme Media: Telaah Kritis Media Massa di Indonesia - Puji Laksono (DIMENSI - Journal of Sociology, 2017)
The images in the mass media present a culture of mass that tends to be discriminatory against certain groups. Various mass cultures presented by the mass media construct a body that unilaterally imaged as the ideal body. The bodies presented by the media tend to represent races with white, straight-haired traits. The practice of mass media racism, makes us should re-question the role of the mass media who carry out the mandate to uphold the public interest. Racism is an example of how the mass media is more concerned with the market than the public interest. The ideal body construction that is represented in every opportunity such as advertising, film, soap operas, and ideal images are created to meet profit targets. The mass media must return to the basic principle for the common good, giving the same space of expression to the entire Indonesian blood spill.